Transverse facial artery occlusion following hyaluronic acid and calcium hydroxyapatite filler injection: a case report - Isabelle Ary Duque; Francisco Jefferson Araújo Elias; Matheus Morais Lima (Surgical & Cosmetic Dermatology)
This case report describes a complication following the use of a filler composed of hyaluronic acid and calcium hydroxyapatite mixed in the same syringe, resulting in vascular occlusion of the right transverse facial artery. The patient developed hypopigmented macules, followed by a reticulated pattern and pustules. Treatment included prednisone, enoxaparin, and hyaluronidase. Due to worsening symptoms, including arterial obstruction confirmed by ultrasound, ultrasound-guided hyaluronidase injection and hyperbaric oxygen therapy were administered. The patient showed a favorable recovery, with regression of vascular complications. This case underscores the importance of early identification and intervention to minimize complications associated with vascular occlusion in aesthetic procedures.